Study guide for use with accounting : the basis for business decisions - Meigs, Walter B.; Meigs, Robert F. (New York : McGraw-Hill, 1981)
This book is a self-study guide designed for use by students taking first course in accounting at either the undergraduate or the graduate level.
usc 14/02/2019
Loans
Keywords: Accounting